Study of Time Correlation and Memory Function for the Derivation of Spectral Density in Plasma - Singh, Akhilesh Kumar; Guragain, Rajesh Prakash; Nakarmi, Jeevan Jyoti; Jha, Lok Narayan; Baniya, Hom Bahadur (Amrit Research Journal, 2023)
This paper is mainly focused on studying time correlation and memory functions in order to determine the spectral density in plasma. The research aims to understand and quantify the noise produced in the plasma as a result of random processes. Noise can arise from various sources, including fluctuations in particle density, temperature, and other plasma parameters. To ensure a fair comparison, the paper appears to keep the cross-sectional area of the plasma which is same for both the Q-Machine and Fusion Reactor. This means that any observed differences in spectral density can be attributed to the inherent characteristics of the two systems rather than differences in plasma volume. It is observed that Fusion Reactor produced more noise in comparison to the Q-Machine. This research seems to contribute to our understanding of plasma physics, specifically in the context of spectral density and noise production, by comparing two different plasma systems. The observed differences in noise levels between the Q-Machine and Fusion Reactor could have important implications for plasma-based technologies and fusion research.